Gaya Retorika Pasangan Kandidat Cagub & Cawagub DKI Dalam Acara Debat Politik - Agusly Irawan Aritonang (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2018)
The local leaders election of DKI is an example of arena in which the candidates play their own political rhetoric to fight for the voters’ heart. Through the political debates, the candidates have the chances to explain who they are, their vision, and the programs they want to do. With the specific rethoric style, a candidate as a political comunicator has a chance to comunicate with the audiences as well as to impress them as the final goal. This study tries to capture how the styles of political rhetoric of each candidate, both candidates for governor and vice governor are demonstrated. A study, with qualitative approach, on debate video of candidates for governor and vice governor of DKI discovers a scheme of rhetoric style of Agus Yudhoyono which combines rhetoric style of exhortive, personal branding, and bureaucratic. Syliviani Murni puts priority on bureaucratic, formal, and exhortive. Basuki Tjahjana Purnama tends to be more spread with combines open, personal branding and also formal and bureaucratic. On the other hand, Djarot is more familiar with the rhetoric style of bureaucratic and exhortive. Anies Basewedan is so intens with the rhetoric style of personal branding and the combination of bureaucracy and exhortive. Sandiaga Uno tends toward rhetoric style of personal branding.